Implementação da troca de emitâncias no booster do SIRIUS para melhoria da eficiência de injeção no anel de armazenamento - Quentino, Jucelio Vitor (2022)
SIRIUS is the newest 4th generation synchrotron light source, built and operated by the Brazilian Synchrotron Light Laboratory (LNLS) at the Brazilian Center for Research in Energy and Materials (CNPEM). The injection system responsible for accumulating electrons in the storage ring comprises two other accelerators, a linear accelerator, and a booster. Storage ring injection efficiency is a constantly optimizing parameter, with the goal of regularly reaching > 95 %. The improvements made so far result in an average efficiency of 86 % with the optimized machine. This work presents the studies and experimental results of the transverse emittance exchange (TEE) implementation in the SIRIUS booster, performed to decrease the injected beam horizontal size and improve injection efficiency. Simulations of injection dynamics in the storage ring were performed, comparing a beam with and without TEE, in addition to a study of adiabaticity conditions and the impact of radiative effects on the quality of the exchange. The TEE implementation was made by modifying the defocusing quadrupoles current at the booster ramp end. The results show a significant improvement in injection efficiency.